2017
DOI: 10.1097/coc.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

c-Met Overexpression in Cervical Cancer, a Prognostic Factor and a Potential Molecular Therapeutic Target

Abstract: Purpose This study aimed to assess the association between pretreatment c-Met overexpression in local-regional advanced cervical cancer patients treated definitively with concurrent chemoradiation (CRT) and treatment outcomes including overall survival (OS), progression free survival (PFS), distant metastases control (DM), and local-regional control (LC). Patients and Methods This IRB approved study included cervical cancer patients treated definitively and consecutively with CRT. Evaluation of cytoplasmic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 36 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Serving as an oncogene, c-Met activates multiple pathways and amplifies the transduction cascade to further mediate tumor cell behaviors [27]. C-Met is also considered as predictive marker of prognosis of tumor patients [2830]. In this study, c-Met was upregulated in OS tissues and cell lines.…”
Section: Discussionmentioning
confidence: 81%
“…Serving as an oncogene, c-Met activates multiple pathways and amplifies the transduction cascade to further mediate tumor cell behaviors [27]. C-Met is also considered as predictive marker of prognosis of tumor patients [2830]. In this study, c-Met was upregulated in OS tissues and cell lines.…”
Section: Discussionmentioning
confidence: 81%
“…RASGRP appears as a miR-34c-3p validated target in the DIANA database, while PDGFB was not validated in the databases consulted. The genes participating in the six cell-signaling pathways potentially regulated by 5p and 3p strands of miR-34 family members are overexpressed in cervical cancer [46,47,48,49,50,51,52,53]. The genes encoding VGEF, RRAS2, PRKCB, RASGRP, and PDGFB involved in the six cell-signaling pathways are not currently reported in cervical cancer; however, they were reported as overexpressed in other carcinomas [54,55,56,57,58], suggesting their participation in carcinogenesis.…”
Section: Resultsmentioning
confidence: 99%
“… 10 Previous studies also found that the physiological function of HGF/c-Met axis revolves around cell motility and invasive growth, and displayed a higher activity in many cancers. 11–14 …”
Section: Introductionmentioning
confidence: 99%
“…10 Previous studies also found that the physiological function of HGF/c-Met axis revolves around cell motility and invasive growth, and displayed a higher activity in many cancers. [11][12][13][14] PHA-665752 is a potent, selective and ATP competitive c-Met inhibitor. As early as in 2003, Christensen et al 15 have found that PHA-665752 could inhibit the c-metdependent phenotype in vitro and exhibit anti-tumor activity in vivo.…”
Section: Introductionmentioning
confidence: 99%